The significance of targeting lysosomes in cancer immunotherapy - Xu, Yanxin; Shao, Bo; Zhang, Yafeng (Frontiers in Immunology, 2024)
Lysosomes are intracellular digestive organelles that participate in various physiological and pathological processes, including the regulation of immune checkpoint molecules, immune cell function in the tumor microenvironment, antigen presentation, metabolism, and autophagy. Abnormalities or dysfunction of lysosomes are associated with the occurrence, development, and drug resistance of tumors. Lysosomes play a crucial role and have potential applications in tumor immunotherapy. Targeting lysosomes or harnessing their properties is an effective strategy for tumor immunotherapy. However, the mechanisms and approaches related to lysosomes in tumor immunotherapy are not fully understood at present, and further basic and clinical research is needed to provide better treatment options for cancer patients. This review focuses on the research progress related to lysosomes and tumor immunotherapy in these